Renewed Focus on RH in the RDN World - Mosley, Mary (MD Conference Express, 2014)
This article discusses the renewed focus on treatment-resistant hypertension (RH), which has been sparked by the interest in catheter renal denervation and the somewhat disappointing results with this interventional approach in the SYMPLICITY HTN trial program.